Exploring the Significance of Publication-Age-Based Parameters for Evaluating Researcher Impact - Ghulam Mustafa (458105) (2023)
In the modern era, bibliometric parameters have become crucial components in evaluating academic productivity. In the last three decades, the scientific community has suggested a variety of bibliometric parameters to rank researchers, such as publication count, citation count, author count, h-index, and its variants. There is an ongoing debate within the scientific community regarding which index provides the most accurate ranking of authors. Currently, the state-of-the-art evaluation of these indices is based on hypothetical scenarios and the limited and unfair distribution of researcher records in the datasets. In addition, these indices are often evaluated using dissimilar datasets, making it challenging to accurately compare their contributions and significance. To comprehensively analyze the performance of each index, it should be evaluated on extensive and balanced datasets. This study focuses on evaluating the effectiveness of some h-index extensions, such as the platinum h, M quotient, AW, AR, V, Ha, Hc, and AWCR indices. For the experiments, this study employed a comprehensive and balanced dataset from the mathematics field to evaluate the performance of these indices. Analysis of these indices was conducted in three stages. First, the correlations among these indices were calculated. A weak correlation between indices suggests that the rankings of authors obtained from these indices are not the same, whereas a strong correlation suggests the opposite. Second, the analysis examines the occurrence of awardees in all ranked lists, using prestigious award winners from four mathematics societies as a benchmark. Based on the analysis, the study reveals that the Ar index performs the best among the evaluated indices, bringing the highest number of awardees to the top 10% of the ranked list, with a maximum of 80%. However, none of the indices can bring all the awardees to the top rankings, indicating that there is no single index that can provide a complete and accurate evaluation of the author’s ranking. Additionally, the study identified that the maximum awardees at the top of all ranked lists belong to the American Mathematical Society (AMS), suggesting that AMS may depend on these indices to determine its award recipients. Furthermore, the AWCR index is more suited to the AMS society by its contribution to returning the highest number of awardees belonging to the AMS society. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2023.3304013